2007
DOI: 10.1186/1471-2164-8-376
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic androgen-dependent gene expression patterns revealed by comparison of genital fibroblasts from normal males and individuals with complete and partial androgen insensitivity syndrome

Abstract: BackgroundTo better understand the molecular programs of normal and abnormal genital development, clear-cut definition of androgen-dependent gene expression patterns, without the influence of genotype (46, XX vs. 46, XY), is warranted. Previously, we have identified global gene expression profiles in genital-derived fibroblasts that differ between 46, XY males and 46, XY females with complete androgen insensitivity syndrome (CAIS) due to inactivating mutations of the androgen receptor (AR). While these differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 20 publications
3
25
0
3
Order By: Relevance
“…The tsDMRs transcend the considerable global differences in DNA methylation between each cell type, since, unlike CAFs, cancer cells undergo extensive hypomethylation (Hansen et al 2011;Berman et al 2012;Kretzmer et al 2015). Notably, the tsDMRs are strongly overrepresented in developmental gene families and genes involved in endocrine hormone secretion, such as TBX3 (Holterhus et al 2007;Beukers et al 2015), suggesting that they are associated with functional roles in cancer progression. Indeed specific tsDMRs were found in known tumor suppressor genes (for example, EHF [Albino et al 2012] and MCC [KohonenCorish et al 2007]) and oncogenes (for example, STEAP2 [Whiteland et al 2014]).…”
Section: Discussionmentioning
confidence: 99%
“…The tsDMRs transcend the considerable global differences in DNA methylation between each cell type, since, unlike CAFs, cancer cells undergo extensive hypomethylation (Hansen et al 2011;Berman et al 2012;Kretzmer et al 2015). Notably, the tsDMRs are strongly overrepresented in developmental gene families and genes involved in endocrine hormone secretion, such as TBX3 (Holterhus et al 2007;Beukers et al 2015), suggesting that they are associated with functional roles in cancer progression. Indeed specific tsDMRs were found in known tumor suppressor genes (for example, EHF [Albino et al 2012] and MCC [KohonenCorish et al 2007]) and oncogenes (for example, STEAP2 [Whiteland et al 2014]).…”
Section: Discussionmentioning
confidence: 99%
“…85 Although it is possible that some of this sexual dimorphism is due to sex chromosome differences, it is possible that some of these differences are due to androgen effects. The presence of an androgen-dependent transcriptome has been identified in genital skin fibroblasts 86 as well as peripheral blood mononuclear cells. 87 An assessment of an androgendependent transcriptome may be of benefit in a number of clinical scenarios but its translation into clinical practice will require major bioinformatic input.…”
Section: Transcriptomics and Its Potential To Clarify The Phenotypementioning
confidence: 99%
“…There was little variation reflected by a standard deviation of 5%. The methylation analysis of 5 labia majora (CAIS), 9 labioscrotal (PAIS) and 1 scrotal (MAIS) fibroblast strains from 46,XY patients with AR mutations and various degrees of AIS (according to table 1 in Holterhus et al [2007]) revealed a striking variability of methylation patterns ranging from 14 up to 82% mean DNA methylation per case (overall mean methylation 41%) with a standard deviation of 20% (online suppl. fig.…”
Section: Bisulfite Pyrosequencing Of the Hoxa5 Promoter Regionmentioning
confidence: 99%